Does global warming threaten small-scale bivalve fisheries in NW Spain?. (September 2022) - Castro-Olivares, A.; Des, M.; Olabarria, C.; deCastro, M.; Vázquez, E.; Sousa, M.C.; Gómez-Gesteira, M.
Abstract: Shellfisheries of the intertidal and shallow subtidal infaunal bivalves Ruditapes decussatus, Ruditapes philippinarum, Venerupis corrugata and Cerastoderma edule are of great socio-economic importance (in terms of landings) in Europe, specifically in the Galician Rías Baixas (NW Spain). However, ocean warming may threaten these fisheries by modifying the geographic distribution of the species and thus affecting productive areas. The present study analysed the impact of rising ocean temperature on the geographical distribution of the thermal comfort areas of these bivalves throughout the 21st century. The Delft3D model was used to downscale climate data from CORDEX and CMIP5 and was run for July and August in three future periods (2025–2049, 2050–2074 and 2075–2099) under the RCP8.5 scenario. The areas with optimal temperature conditions for shellfish harvesting located in the middle and outer parts of the rias may increase in the near future for R. decussatus, V. corrugata and C. edule and decrease in the far future for R. philippinarum . Moreover, shellfish beds located in the shallower areas of the inner parts of the Rías Baixas could be affected by increased water temperature, reducing the productive areas of the four species by the end of the century. The projected changes in thermal condition will probably lead to changes in shellfish harvesting modality (on foot or aboard vessels) with further socio-economic consequences. Graphical abstract: Image 1 Highlights: Change impact projected on important socioeconomic intertidal shellfish species. Rising water temperature will displace thermal comfort areas. Thermal comfort conditions in the middle and outer parts of the rias may improve. Shellfish areas in the inner parts could be negatively impacted by ocean warming. Harvesting method will likely be affected.